Seroprevalence to herpesviruses in patients with primary brain gliomas - T. A. Zykova; O. I. Kit; E. E. Rostorguev; E. A. Shevyakova; N. S. Kuznetsova (Исследования и практика в медицине)
Purpose of the study. The purpose of the study was to assess the level of seroprevalence and the frequency of detection of serological markers of acute herpesvirus infection in patients with PGBT in comparison with those in patients with chronic non-tumor diseases.Materials and methods. Before conducting antitumor therapy, the blood serum of 42 patients with PGBT (the main group) was studied. The comparison group consisted of 137 patients with chronic non-tumor diseases. Antibodies of classes M and G to herpes simplex virus types 1, 2 (HSV-1,2), cytomegalovirus (CMV), Epstein-Barr virus (EBV), human herpes virus type 6 (HHV-6) were determined by ELISA using JSC "Vector-Best" reagent kits.Results. Among patients with PGBT, seropositive for HSV-1,2 were 95.2%, CMV — 92.9%, EBV — 100%, HHV-6-40.5% of patients. No statistically significant differences in seroprevalence and the presence of markers of acute infection (IgM) were found either in comparison with non-tumor diseases or depending on the malignancy grade. Antibodies to HSV-1,2, CMV and EBV in patients with gliomas were significantly more often found in the medium range, and in the comparison group — in the high values of coefficient of positivity (CP) for IgG. In all the studied groups, antibodies to HHV-6 were determined statistically significantly less frequently than to other herpes viruses.Conclusion. The absence of statistically significant differences in seropositivity between groups of patients and their presence between pathogens is most likely a reflection of general trends in the population, and the question of the involvement of various representatives of the Herpesviridae family in neuro-oncogenesis of primary glial brain tumors still remains open.